Effect of Polymorphisms of ABCB1 and MTHFR on Methotrexate-Related Toxicities in Adults With Hematological Malignancies - Han, Jian; Liu, Lu; Meng, Li; Guo, Huan; Zhang, Jin; Han, Zhi-Qiang; Hong, Zhen-Ya (Frontiers in Oncology, 2021)
Pharmacogenomics of MTX contributes to inter-individual differences in toxicity. We aimed to evaluate the impact of SNPs within the MTX pathway genes on MTX-induced toxicity in adults with hematological malignancies. Patients were genotyped for MTHFR rs1801131, MTHFR rs1801133, and ABCB1 rs1045642 by FISH. Patients with MTHFR rs1801133T allele had significantly higher risk of hematopoietic toxicity than those with CC genotype (p=0.003). With regard to MTHFR rs1801131, patients with C allele had significantly lower risk of hematopoietic toxicity than those with AA genotype (p=0.044). This study identifies a significant role of SNPs in the MTX pathway gene ABCB1 and MTHFR on MTX-related toxicity. Such results could enable tailored therapy based on a pharmacogenomics approach in order to prevent or reduce toxicity. Genotyping prior to treatment is valuable with the aim of adapting MTX therapy and thus reducing toxicity.